Evaluation Of Intermittent Preventive Treatment Of Malaria In Pregnancy (IPT) Implementation In The Kumasi Ashanti Region, Ghana. - Priscilla Anima, Siaw (2011)
Malaria is a serious public health problem that affects both the young and old especially the vulnerable ones being children and pregnant women. Again, prevention of the serious health impact associated with malaria during pregnancy represents one of the pending public health goals of WHO policy as well as the Ghana Roll Back Preventive Treatment (IPT) is a preventive measure adopted for the prevention of malaria in pregnancy. Objective The primary objective of this study is to assess the IPT of malaria in pregnancy in relation to the processes, outcomes and impact of the policy in the Kumasi metropolis of the Ashanti Region – Ghana. Methodology The study was a descriptive qualitative and quantitative cross sectional study supported with health facilities records review. The data were collected in August 2008 using household interviews during which 400 respondents (280 pregnant women and 120 nursing mothers who have delivered between January and June, 2008) were sampled using a EPI cluster sampling technique were interviewed. Seventy (70) midwives and 22 key informants at post in some selected health facility within the Manhyia North, the Subin and the Bantama Sub-metros were in-depth interviewed with close-ended questionnaire. Forty-seven (47) health facilities which offer maternity services were also surveyed with the aid of a checklist. A review of the Kumasi Metropolis health records was also conducted. Seven descriptive processes, out come and impact indicators were used in the study. These included: training and KAP of midwives, ANC utilization in the metropolis, the KAP of pregnant mothers and midwives towards malaria in pregnancy, IPT coverage, management supply of SP, the incidence of adverse effects of SP in pregnant mothers on IPT and the incidence of LBW as well as maternal aneamia.